一种改善Ai智慧摄影场景优化策略的实现方法 (2023)
本发明公开了一种改善Ai智慧摄影场景优化策略的实现方法，能够最大程度地减少手机在自动场景优化中出现的失误，提高手机拍出好照片的成功率，为手机智慧摄影提供实时准确的拍摄技法和视觉优化方案。本发明的主要用途在于，通过将【主体识别】从【场景识别】中分离出来单独进行主体优化的方式，可以确保被摄主体的拍摄效果和视觉效果不受外围人为的场景优化因素的干扰，突出被摄主体在摄影画面中的独立性和真实性；同时将场景识别由原有的单一模式修正为多个组成部分的多重场景识别模式，可以获得更加准确的取景画面实际场景描述，以便于实施更加精准有效的组合场景优化效果；基于这种主体优化和场景优化的双重策略，最终实现能模拟摄影师一样去运用实拍经验和后期技巧的Ai智慧拍摄技能。 The invention discloses a method for improving the Ai intelligent photography scene optimization strategy, which can reduce the mistakes of the mobile phone in the automatic scene optimization to themaximum extent, improve the success rate of the mobile phone to take good pictures, and provide real-time and accurate shooting technique and visual optimization scheme for the mobile phone intelligent photography. The main purpose of the invention is to ensure that the shooting effect and the visual effect of the subject are not disturbed by the peripheral artificial scene optimization factors, and to highlight the independence and the authenticity of the subject in the photographic picture by sep